1982
DOI: 10.7601/mez.33.181
|View full text |Cite
|
Sign up to set email alerts
|

Studies on medically important flies in Thailand : VIII. Report on 73 species of muscid flies (excluding Muscinae and Stomoxyinae) with the taxonomic keys (Diptera : Muscidae)

Abstract: In 1975, the survey on the medically important fiies was made in the different geographical parts of Thailand. Since that time, all the fly specimens have been examined and identified. Most of them have reported as series under the same title (Tumrasvin et at., 1976-1979). rn this paper we are reporting three subfamilies, Phaoniinae, Lispinae and Fanniinae respectively. Phylogenetic systems identifying subfamilies and genera in this paper cited Emden's system (Ernden, 1965) in connection ",ith former paper on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…This finding parallels previous results indicating that S. indicus can be distinguished by the adult external morphology (yellowish colour of tibiae and tarsi) (Tumrasvin and Shinonaga 1978). Additionally, the phylogenetic relationship based on cytochrome c oxidase subunit I (COI) showed that S. pullus and S. uruma have a closer genetic relationship than either has with S. indicus (T.C.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This finding parallels previous results indicating that S. indicus can be distinguished by the adult external morphology (yellowish colour of tibiae and tarsi) (Tumrasvin and Shinonaga 1978). Additionally, the phylogenetic relationship based on cytochrome c oxidase subunit I (COI) showed that S. pullus and S. uruma have a closer genetic relationship than either has with S. indicus (T.C.…”
Section: Discussionsupporting
confidence: 79%
“…The traps were placed at the collection sites from 6:00 AM to 6:00 PM over a two-day-period (Changbunjong et al 2012). Species were identified with a stereomicroscope based on the taxonomic key of Zumpt (1973) and Tumrasvin and Shinonaga (1978).…”
Section: Specimen Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before identification, the flies were anesthetized by placing the cages in a refrigerator set at 4 °C for 15 min. The anesthetized flies were identified following the taxonomic keys 7,21 . M. domestica and C. megacephala were segregated into separate cages (30×30×30 cm) screened with black cloth.…”
Section: Collection and Maintenance Of Fliesmentioning
confidence: 99%